Keterlibatan Instansi Swasta dalam Transformasi Bangunan Milik Negara: M Bloc Space Jakarta - Bismo Aulia Prianggara; Wiwik Dwi Pratiwi (Arsitektura : Jurnal Ilmiah Arsitektur dan Lingkungan Binaan, 2023)
This research describes the transformation of state-owned buildings in M Bloc Space Jakarta, specifically the involvement of private agencies in decision making.This needs to be studied because many state-owned building assets have long been neglected and have the potential to be converted into new, more relevant functions. This study uses a descriptive method in analyzing the involvement of public agencies in making decisions about the functions of the new building. Agency theory is applied to examine the involvement of institutions and stakeholders in managing state-owned building transformation. The results of this study show that the transformation of state-owned buildings into public spaces is based on the owner’s economic interests aligned with the shared values and vision of the building operators.